National role conceptions in a new millennium: defining a place in a changing world - Grossman, Michael; Schortgen, Francis; Friedrichs, Gordon (Taylor & Francis Group, 2022)
Cover -- Endorsements -- Half Title -- Series Page -- Title Page -- Copyright Page -- Contents -- List of contributors -- 1. Introduction: Defining Roles in a Polycentric World -- SECTION I: National Roles -- 2. Shrinking the US Leadership Role: Populism and the Change of Domestic and International "Others" -- 3. The Evolution of Russia's National Role Conceptions: From Cooperation to Great Power Competition -- 4. Taking Center Stage: China's New Role Assertiveness in the 21st-Century International System -- 5. A Tenuous Island: The Destabilization of Britain's Role in the International System of the 21st Century -- 6. Berlin, We Have a Problem: Germany's Role Adaptability and the Transatlantic Security Community -- 7. Contesting Japan's International Role: The Responses of Japanese Non-governmental Organizations to the Transformation of Japanese ODA Policy -- SECTION II: Institutional Roles -- 8. The European Union's Self-conception of Its Roles in Global Affairs -- 9. NATO's Role Transitions in a Changing International System -- 10. ASEAN: The Center of Asian Regionalization? A Model for a Global Future? -- 11. The Organization of American States' Role as Facilitator of Democracy Promotion: Persuasion and Social Influence during the Political Crisis in Venezuela -- 12. Conclusion: Turbulence in the 21st-century International Order -- Index.
Description based on publisher supplied metadata and other sources
Keywords: Erde